Hydrodynamics of Exploding Foil X-Ray Lasers with Time-Dependent Ionization Effect - 王玉 苏丹丹 李英骏 (Plasma science & technology, 2016)
A simple modified model is presented based on R. A. London＇s self-similarity model on time-independent ionization hydrodynamics of exploding foil X-ray lasers. In our model, the time-dependent ionization effect is under consideration and the average ion charge depends on the temperature. Then we obtain the new scaling laws for temperature, scale length and electron density, which have better agreement with experimental results.